Minimalisasi Defect Produk Granite Tile Pada Proses Sorting & Polishing Dengan Pendekatan Root Cause Analysis (RCA) (Studi Kasus di PT. Niro Ceramic Nasional Indonesia, Bogor–Jawa Barat ) - Irman Maulana; Bambang Suhardi Waluyo; Tri Widodo (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
Competition in the industry makes manufacturing companies do continuous improvement of production in order to achieve good quality. PT. XYZ is a company engaged in the manufacturing industries that produce granite tile. The problems that often arise on the production floor, especially in the process of sorting and polishing that is, the high defect products produced in the process. The purpose of this study is to minimize damage to the product on the S & P, Useful and finished product quality improvement plans. To support solving this problem, researchers used a method approach Root Cause Analysis (RCA). In the histogram obtained from the check sheets, Pareto diagrams visible damage in the S & P damage type of disability the most dominant is the Crack (57%), followed Thick (18%), Glaze Drop (11%), Black Coring (8%), and the last is the Scraper Defect (6%). From the research, a result that most of the damage is Crack. Factors causing these defects are the factors that cause deviations quality raw materials such factors, factors working methods irregularities in the implementation of the work, a factor that is less engine preventive maintenance, factor of fewer operators do not obey the standard factory operations. From the productivity results in the S & P, generate some suggestion in terms of minimizing the product is defective is implementing kaizen.Â Keywords: Root Cause Analysis (RCA), Application of Process Improvement, Kaizen, 5S, Granite Tile.Â